2017
DOI: 10.1016/j.brq.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive routines and international patent performance

Abstract: Patents on an international level are essential for firm results. Accordingly, the use of external sources of knowledge acquires crucial importance to get global innovations and create competitive advantages. For that reason, the literature has highlighted the strategic role of the absorptive capacity construct. We enrich the treatment of the absorptive capacity phases including the moderating effects between routines associated to the traditional potential-realized absorptive capacities. Taking into account e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 145 publications
(276 reference statements)
0
9
0
Order By: Relevance
“…In particular, R&D intensive SMEs can prefer technology sourcing to other types of open innovation strategies ( Lee et al, 2017) as this strategy allows to exploit existing synergies among different knowledge bases (Messeni Petruzzelli and Murgia, 2020). Acquisition of foreign patents is a specific technology sourcing strategy (Garcia-Muina and Gonzales-Sanchez, 2017). Firms stand to benefit from the combination of external knowledge produced in different geographies when they are involved in the development of complex innovations (Capaldo et al, 2017) while searching across different knowledge domains 15 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, R&D intensive SMEs can prefer technology sourcing to other types of open innovation strategies ( Lee et al, 2017) as this strategy allows to exploit existing synergies among different knowledge bases (Messeni Petruzzelli and Murgia, 2020). Acquisition of foreign patents is a specific technology sourcing strategy (Garcia-Muina and Gonzales-Sanchez, 2017). Firms stand to benefit from the combination of external knowledge produced in different geographies when they are involved in the development of complex innovations (Capaldo et al, 2017) while searching across different knowledge domains 15 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These include the acquisition of foreign intellectual property (IP) that assist firms to access external knowledge considered unique. They can also complement internal knowledge (Garcia-Muina and Gonzales-Sanchez, 2017) and crucially cannot be accessed by local competitors, as it is generated in geographically distant locations (Vertesy et al, 2017). Therefore, acquiring foreign IP can be appealing to R&D intensive firms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyer and Nobeoka (2000) concluded that Toyota’s knowledge-sharing routines with partners result in improved competitive advantage. García-Muiña and González-Sánchez (2017) and Nieto and Santamaría (2017) provide empirical evidence of the role that assimilation routines have, making cooperation agreements an efficient source of external knowledge. Schilke and Goerzen (2010) also highlight that interorganizational learning capabilities represent a key advantage in alliances and have a positive impact on the amount of resources obtained from them.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As seen in Table II, the experiential dimension has received less attention and it has been poorly defined. Coherently, the exploitation phase of the absorptive capacity has suffered from the same problems (García-Muiña and González-Sánchez, 2017). By contrast, the other three dimensions have been studied in depth.…”
Section: Open Innovation Approach and Museumsmentioning
confidence: 99%